Sistem Informasi Pemetaan Objek Wisata Pesisir Kota Manado, Kota Bitung, dan Kab. Minahasa Utara Berbasis Web - Aditya Lapu Kalua; Samuel Pondaag; Fadhila Mohune (Journal of Information Technology, Software Engineering and Computer Science, 2023)
The coastal areas in Manado City, Bitung, and North Minahasa Regency in North Sulawesi Province have great tourism potential. However, currently there is no information system that provides complete and easily accessible information for tourists. Therefore, the development of an information system for tourist attractions along the coast is needed to present detailed and easily accessible information. In its development, this information system uses the RAD (Rapid Application Development) method as a software development approach. My Maps is used as a tool for seismic location of tourist attractions. This system provides comprehensive information about locations, entrance ticket prices, operating hours, facilities, descriptions, and available pictures of tourist attractions. This information system makes it easy for tourists to access information to plan visits to the coasts of Manado, Bitung and North Minahasa. The test results that in the application that has been tested there are no errors from the entire function, so the test results get a score of 100% according to the function of the application created.